LAYANAN SALES ORDER PADA PT SEMEN INDONESIA LOGISTIK - Maharani, Shinta Puspa; Sukaris (Universitas Sarjanawiyata Tamansiswa, 2024)
PT Semen Indonesia Logistik is engaged in Distribution & Retail by providing logistics services for the delivery of cement products to customers. It can be outlined that the level of service quality is the main key for the company becomes the main key for the company. The purpose of this research is to maximize quality of service at the company PT Semen Indonesia Logistics with the findings of the the problem of the fios system which still cannot intervice data with the CSMS system, resulting in several SOs that must be done. with the CSMS system, resulting in several Sales Order that must be made manually because the Fios system is still manually because the Fios system is still under development. Impact resulting from this problem, is the delay in making sales orders. sales orders, scheduling is not according to standards, and even delays in the delivery of goods. Factors that influence are such as, lack of human resources, a system that is still manual, the occurrence of input errors in the SO related to the destination address, vehicle type, load type, and even delays in delivery of goods. with destination address, type of vehicle, type of cargo, quantity, this is caused by a lack of coordination between sales teams. caused by a lack of coordination between the sales team, operations, and also the warehouse. the warehouse. With this problem, research was conducted with hope to provide solutions and also improvements in service quality services